The Future of Transportation - Autonomous Vehicles - Bunghez, Corina Larisa (International Journal of Economic Practices and Theories, 2015)
Autonomous vehicles are currently among the most important activities in research and transport industry development. Being at the stage of prototypes undergoing extensive testing, these vehicles have the potential to replace human drivers in the next decade. This survey analyses all the aspects linked to the implementation of these new technologies. One by one, we will analyse the benefits, the costs and the risks that will arise following the transition from human driven automobiles to those operated completely autonomous. Moreover, another important element of this paperwork is the analysis of predictions and future trends in this field. We will highlight the changes produced at the level of transport activities and also the way in which these innovations will transform our society from other points of view. The impact that the introduction of autonomous vehicles will have on people will be a very strong one and, according to predictions and estimations, this transformation is closer than we think.